Access to drugs and the situation of the pharmaceutical market in Ecuador [Acceso a medicamentos y situación del mercado farmacéutico en Ecuador] - Galarza Maldonado, Claudio (2014)
In the area of public health, it is fundamental to understand the structure and dynamics of the Ecuadorian pharmaceutical market, its segmentation between the public and private sectors, and its relationship with supply and demand, both for generic and brand-name drugs. To achieve this, an observational descriptive study was conducted with information obtained from the available scientific, institutional, technical-administrative, and economic databases. Furthermore, the scientific information concerning the Ecuadorian and regional pharmaceutical market was reviewed through the PubMed and Ovid search engines. In Ecuador, 69.6% of dispensed drugs are brand-name and 30.4% are generics. Of all registered drugs in the country, 1 829 (13.6%) are considered over-the-counter and 11 622 (86.4%) are for sale under medical prescription. In terms of sales, 93.15% correspond to brand-name drugs and only 6.85% to generics. Ninety percent of the pharmacies are located in urban areas and only 10% in rural areas. In the last five years, prices have increased by 12.5% for brand-name drugs and 0.86% for generics. Brand-name drugs are dispensed and consumed 2.3 times more than generics. The majority of pharmacies are located in urban areas, showing that there is a relationship between purchasing power and access to drugs. Although the regulatory authority stipulates that 13% of drugs should be over-thecounter, approximately 60% of the population acquires drugs without a medical prescription.